Accuracy and reproducibility of aortic annular measurements obtained from echocardiographic 3D manual and semi-automated software analyses in patients referred for transcatheter aortic valve implantation: implication for prosthesis size selection. (6th February 2018) - Stella, Stefano; Italia, Leonardo; Geremia, Giulia; Rosa, Isabella; Ancona, Francesco; Marini, Claudia; Capogrosso, Cristina; Giglio, Manuela; Montorfano, Matteo; Latib, Azeem; Margonato, Alberto; Colombo, Antonio; et al.
Abstract: Aims: A 3D transoesophageal echocardiography (3D-TOE) reconstruction tool has recently been introduced. The system automatically configures a geometric model of the aortic root and performs quantitative analysis of these structures. We compared the measurements of the aortic annulus (AA) obtained by semi-automated 3D-TOE quantitative software and manual analysis vs. multislice computed tomography (MSCT) ones. Methods and results: One hundred and seventy-five patients (mean age 81.3 ± 6.3 years, 77 men) who underwent both MSCT and 3D-TOE for annulus assessment before transcatheter aortic valve implantation were analysed. Hypothetical prosthetic valve sizing was evaluated using the 3D manual, semi-automated measurements using manufacturer-recommended CT-based sizing algorithm as gold standard. Good correlation between 3D-TOE methods vs. MSCT measurements was found, but the semi-automated analysis demonstrated slightly better correlations for AA major diameter ( r = 0.89), perimeter ( r = 0.89), and area ( r = 0.85) (all P < 0.0001) than manual one. Both 3D methods underestimated the MSCT measurements, but semi-automated measurements showed narrower limits of agreement and lesser bias than manual measurements for most of AA parameters. On average, 3D-TOE semi-automated major diameter, area, and perimeter underestimated the respective MSCT measurements by 7.4%, 3.5%, and 4.4%, respectively, whereas minor diameter was overestimated by 0.3%. Moderate agreement for valve sizing for both 3D-TOE techniques was found: Kappa agreement 0.5 for both semi-automated and manual analysis. Interobserver and intraobserver agreements for the AA measurements were excellent for both techniques (intraclass correlation coefficients for all parameters >0.80). Conclusion: The 3D-TOE semi-automated analysis of AA is feasible and reliable and can be used in clinical practice as an alternative to MSCT for AA assessment.